Pharmacokinetics of free oxytetracycline and oxytetracycline loaded cockle shell calcium carbonate-based nanoparticle in BALB/c Mice - Idris, Sherifat Banke; Abdul Kadir, Arifah; Abdullah, Jesse F. F.; Ramanoon, Siti-Zubaidah; Abdul Basit, Muhammad; Abubakar, Md Zuki Z. A. (Frontiers, 2020)
The development and utilization of nano-antibiotics is currently gaining attention as a possible solution to antibiotic resistance. The aim of this study was therefore to determine the pharmacokinetics of free oxytetracycline (OTC) and oxytetracycline loaded cockle shell calcium carbonate-based nanoparticle (OTC-CNP) after a single dose of intraperitoneal (IP) administration in BALB/c mice. A total of 100 female BALB/c mice divided into two groups of equal number (n = 50) were administered with 10 mg/kg OTC and OTC-CNP, respectively. Blood samples were collected before and post-administration from both groups at time 0, 5, 10, 15, and 30 min and 1, 2, 6, 24, and 48 h, and OTC plasma concentration was quantified using a validated HPLC-UV method. The pharmacokinetic parameters were analyzed using a non-compartment model. The Cmax values of OTC in OTC-CNP and free OTC treated group were 64.99 and 23.53 μg/ml, respectively. OTC was detected up to 24 h in the OTC-CNP group as against 1 h in the free OTC group following intraperitoneal administration. In the OTC-CNP group, the plasma elimination rate of OTC was slower while the half-life, the area under the curve, and the volume of the distribution were increased. In conclusion, the pharmacokinetic profile of OTC in the OTC-CNP group differs significantly from that of free OTC. However, further studies are necessary to determine the antibacterial efficacy of OTC-CNP for the treatment of bacterial diseases.